ANTIBACTERIAL ACTIVITY OF ETHANOLIC EXTRACT AND INFUSE OF Bauhinia variegata LEAVES AGAINST Streptococcus pyogenes - istiqamatush sholihah (Universitas Muhammadiyah Surakarta, 2017)
Bauhinia variegata is a plant that has many virtues and widely grown in Indonesia. Yet the virtues and uses are still limited as the shade and ornamental plant. The purpose of this study is to determine the antibacterial ethanol extract activity and the infuse of Bauhinia Variegata leaves toward Streptococcus pyogenes and to determine the classes of compounds that have antibacterial activity. Bauhinia variegata leaves are extracted by maceration and infundation with 96% ethanol and distilled water. The test method of antibacterial activity is used disc difusson Kirby Bauer methods. The Analyses of the compounds which are contained in the Bauhinia Variegata leaves are done by TLC (Thin Layer Chromatography) and test tubes. The results showed that ethanol extract and infuse of Bauhinia Variegata leaves has no antibacterial activity toward Streptococcus pyogenes. TLC results and test tubes showed that the ethanol extract of Bauhinia Variegata leaves contain tannins, saponins, terpenoids, and alkaloids. While, the infuse of Bauhinia variegata leaves are saponins and alkaloids. Keywords: Bauhinia variegata, antibacterial, Streptococcus pyogenes, maceration, infundation.